Sibling Dynamics in the Digital Era: A Qualitative Study on the Influence of Social Media on Adolescent Sibling Relationships - Joseph, Abhilash; L. Chavez, Maria Lourdes (Asian Horizons, 2025)
This qualitative study explores the influence of social media on adolescent sibling relationships in the digital era. The research examines how platforms such as Instagram, WhatsApp, Facebook, and TikTok shape sibling communication, emotional bonds, and conflict resolution. By analyzing adolescents’ experiences, the study identifies both the strengthening effects of digital connectivity and the challenges introduced by online rivalry and social comparison. It addresses a critical research gap in understanding sibling dynamics mediated through digital platforms, offering insights into how social media redefines familial bonds.